Gender and religious interpretation in Malaysian social media: sentiment and semantic representation analysis / SS. Sharifah Syahirah, Rus Shafinas Shafie and Zarihan Samsudin - SS., SS. Sharifah Syahirah; Shafie, Rus Shafinas; Samsudin, Zarihan (Centre for Media and Information Warfare Studies, 2017)
The social media has become the communication platform of choice where netizens are engaged with political issues, economics, social, cultural and even personal. The new media has a deep impact and seems to assist in the effort of winning the hearts and minds of netizens. Issues that are close to the hearts of netizens especially in terms of religion and gender are widely discussed using the new media. Therefore, the main objective of this paper is to discuss the gender and religious interpretation and discourse in Malaysian social media within sentiment and gender representation semantic framework. This article analyses four keywords; aurat, poligami (polygamy), tanggungjawab suami/isteri (huband's/wife's responsibility) and taat suami/isteri (loyalty to husband/wife). Sentiment analysis focuses on three categories; positive, neutral and negative sentiments while taking into consideration the concept of power relations particularly 'power over' and 'power with'. While, semantic representation analysis applies substative equality and hegemonic masculinity concepts. This study employs both qualitative as well as quantitative research methods. The data from social media was extracted by using Trackur, Social Mention and facebook tracking applications. The findings of the study reveal that there are more negative sentiments in the form of 'power over' rather than in the forms of 'power with' and 'power within'. The study also found that most perceptions and intrepretations pertaining to aurat leans heavily towards hegemonic masculinity of religious interpretation while poligami leans toward the unacceptance of the polygamous practice as well as upholds substantive equality interpretation.